2021
DOI: 10.1186/s13550-021-00869-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metastatic disease using [18F]PSMA-1007 PET/CT for primary prostate cancer staging

Abstract: Background Accurate prostate cancer imaging is critical for patient management. Multiple studies have demonstrated superior diagnostic accuracy of [68Ga]-PSMA-11 PET/CT over conventional imaging for disease detection, with validated clinical and biochemical predictors of disease detection. More recently [18F]PSMA-1007 offers theoretical imaging advantages, but there is limited evidence of clinical and biochemical predictors of scan findings in the staging population. This study investigates the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 40 publications
(36 reference statements)
2
30
1
Order By: Relevance
“…We found a moderately strong relationship between all Tc‐PSMA uptake measures in the primary tumor and pSUV and ISUP grade, the likelihood of metastatic disease, and PSA. The relationship between pSUV and biopsy has been noted in both a previous Tc‐PSMA study and several Ga‐PSMA studies 6,26 . Other studies have shown a relationship between pSUV and histopathology at the surgery for Ga‐PSMA 27 .…”
Section: Discussionmentioning
confidence: 69%
“…We found a moderately strong relationship between all Tc‐PSMA uptake measures in the primary tumor and pSUV and ISUP grade, the likelihood of metastatic disease, and PSA. The relationship between pSUV and biopsy has been noted in both a previous Tc‐PSMA study and several Ga‐PSMA studies 6,26 . Other studies have shown a relationship between pSUV and histopathology at the surgery for Ga‐PSMA 27 .…”
Section: Discussionmentioning
confidence: 69%
“…Giesel et al denoted no significant difference between 18 F-PSMA-1007 and 18 F-DCFPyL 17 . Consistent with 68 Ga-PSMA-11 and 18 F-DCFPyL, the SUV max of the focal lesion was positively correlated with the grade groups and serum PSA level 14,15,33,40,42,51–53 …”
Section: Discussionmentioning
confidence: 87%
“…14,15,17,[29][30][31][32][33][34]36 Of all included studies, the Gleason scores were between 7 and 9 in 12 studies (Table 1). 14,15,17,18,[29][30][31][32][33][34][35][36] Technical Aspects of 18 F-PSMA-1007 PET/CT in the Included Studies…”
Section: Basic Characteristics Of Primary Prostate Cancer Patients Fr...mentioning
confidence: 99%
See 2 more Smart Citations